The Venous Distension Sign: A Diagnostic Sign of Intracranial Hypotension at MR Imaging of the Brain - Farb, R.I.; Forghani, R.; Lee, S.K.; Mikulis, D.J.; Agid, R. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: Patients with intracranial hypotension (IH) demonstrate intracranial venous enlargement with a characteristic change in contour of the transverse sinus seen on routine T1-weighted sagittal imaging. In IH, the inferior margin of the midportion of the dominant transverse sinus acquires a distended convex appearance; we have termed this the venous distension sign (VDS). This is distinct from the normal appearance of this segment, which usually has a slightly concave or straight lower margin. This sign is introduced, and its performance as a test for the presence of this disease is evaluated.MATERIALS AND METHODS: The transverse sinuses on T1-weighted sagittal imaging of 15 patients with IH and 15 control patients were independently assessed in a blinded fashion by 3 readers for the presence of a VDS. A present or absent VDS was determined for each patient by each reader, and a consensus result for each patient was determined by unanimity or majority rule.RESULTS: Using the VDS, the readers correctly identified 93% (14 of 15) of the IH patients and similarly 93% (14 of 15) of the control patients. There was a high rate of agreement among the readers for the interpretation of the VDS (multirater κ = 0.82). The overall sensitivity of the VDS for the diagnosis of intracranial hypotension was 94%. Specificity was also 94%.CONCLUSION: The VDS appears to be an accurate test for the presence or absence of IH and may be helpful in the evaluation of these patients.